Hybrid Dielectric Metasurfaces for Enhancing Second-Harmonic Generation in Chemical Vapor Deposition Grown MoS2Monolayers - Loechner, Franz J. F.; George, Antony; Koshelev, Kirill; Bucher, Tobias; Najafidehaghani, Emad; Fedotova, Anna; Choi, Duk-Yong; Pertsch, Thomas; Staude, Isabelle; Kivshar, Yuri; Turchanin, Andrey; Setzpfandt, Frank (ACS Photonics, 2021)
The coupling of two-dimensional materials with optical metasurfaces is a promising avenue to enhance the advantageous properties of both platforms. Here we integrate an ultrathin monolayer of the transition metal dichalcogenide (TMD) MoS2, grown by chemical-vapor deposition, with a silicon metasurface, to obtain a hybrid system with enhanced nonlinear response. To this end, we utilize a metasurface exhibiting resonances with high quality factors, which provides increased optical fields. Using the nonlinearity of the TMD monolayer, these resonantly enhanced fields enable more efficient nonlinear frequency conversion. In particular, we experimentally observe an enhanced efficiency of second-harmonic generation in our hybrid structure. By comparing second-harmonic generation using different photonic resonances, we furthermore identify optimized conditions for the spatial distribution of the local optical fields to maximize the nonlinear response. Our results enable the precise design of hybrid structures consisting from TMDs and metasurfaces for future applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2D material; chemical vapor deposition; dielectric metasurface; Fano resonance; MoS; second-harmonic generation; transition metal dichalcogenides